EVALUATION OF CSF FERRITIN AS AN EARLY MARKER FOR DIFFERENTIATING MENINGITIS IN PEDIATRIC PATIENTS - Sharma, Shikha; Dabla, Pradeep Kumar (BALI MEDICAL JOURNAL; Vol 3 No 2 (2014), 2014)
Background and Objectives : - Bacterial meningitis is a medical emergency with a potential for  serious neurological damage or even death. Rapid diagnosis is important and henceforth critical for  the early intervention by antibiotic therapy to prevent complications. Therefore the aim of the present  study was to evaluate CSF ferritin levels in children with different etiologies of meningitis. Materials and Methods : - 65 children (1-124 months) with suspected meningitis admitted at Chacha Nehru BalChikitsalya hospital were included in the study. CSF sample was analyzed for glucose, protein, cell count, ferritin, gram stain and culture.  Results: - Based on the laboratory findings the 65 children were classified into 3 groups: 21 cases had bacterial meningitis, 18 had aseptic (viral) meningitis and 26 cases as the no-meningitis group. A significant relationship was observed between age and ferritin level in the non-meningitis group (p<0.05). CSF ferritin in bacterial meningitis group was 34.80 ±11.20 ng/mL and was significantly higher than the aseptic meningitis group. Cut off value of ferritin to differentiate meningitis vs. no-meningitis group was estimated at 18.2ng/ml with a sensitivity of 94.9% and specificity of 96.2 %. However on differentiating bacterial from aseptic meningitis cutoff value was 20.3 ng/mL with a sensitivity of 98% and specificity of 33.3%.  Conclusion : - CSF ferritin levels were found to be significantly different between the meningitis and the no-meningitis groups. However due to low specificity it may not prove useful for the early differentiation of different types of meningitis. Further studies are required on a larger sample size before we can substantiate our findings.
Keywords: CSF ferritin, bacterial meningitis, viral meningitis, pleocytosis, antibiotic therapy